Measurement of the Λb0 lifetime in the exclusive decay Λb0→J/ψΛ0 in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Aoki, M.; Askew, A.; Atkins, S.; et al. (American Physical Society (APS), 2012)
We measure the Λb0 lifetime in the fully reconstructed decay Λb0→J/ψΛ0 using 10.4fb -1 of pp̄ collisions collected with the D0 detector at √s=1.96TeV. The lifetime of the topologically similar decay channel B0→J/ψKS0 is also measured. We obtain τ(Λb0)=1.303±0.075(stat)±0.035(syst)ps and τ(B0)=1.508±0.025(stat)±0.043(syst)ps. Using these measurements, we determine the lifetime ratio of τ(Λb0)/τ(B0)=0. 864±0.052(stat)±0.033(syst). © 2012 American Physical Society.